Game-related statistics that discriminate winning and losing teams from the world championships in Sain in 2014 - Causevic, D. (Homosporticus, 2015)
Basketball is one of the most popular sports today, and therefore the sport that is the subject of much research. The aim of this study was to determine on the basis of which basketball performance indicators can be discriminate winners from losers at the finals of big events. The sample represented 76 matches of world championships in Spain in 2014, of which the official statistical parameters downloaded from FIBA. The results of discriminative analysis showed that the winners can be discriminate from defeated statistic significantly in defensive rebounds (SC = .68), successful 3-points (SC = .49), unsuccessful 2-points (SC = -. 41), biggest lead (SC = .37) and offensive rebounds (SC = .35). The results could be useful to trainers in the preparation and to prepare training programs for this kind of competition.